Modes of representation of women in documentaries on extrajudicial executions in Colombia - Calvo de Castro, Pablo; Eusse Garcés, Laura Alexandra; Alzate Giraldo, Alberto Alejandro (Comunicación y Género [Communication and Gender], 2021)
This paper analyzes the representation of women in documentaries about extrajudicial executions in Colombia. This work is included in an investigation into the representation and discursive strategies of the social groups of women victims of the conflict in mass media, social networks and in audiovisual documentary works. The latter are constituted as a fundamental tool for social change. Through a qualitative methodology, we use film analysis and analyze six titles on extrajudicial executions within the Colombian conflict. This in order to verify that women are the main protagonists in the search for truth. We also want to analyze how the construction of documentary discourse sometimes reduces that prominence.